An expansion formula for the H-function of two variables - Saxena, R. K.; Kalla, S. L. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The object of this note is to evaluate an integral associated with Bessel polynomials and the H-function of two variables and to apply it in proving an expansion formula for the H-function of two variables in series of product of the Bessel polynomials and a related H-function of two variables. The results obtained are of general character and the integrals in series expansions associated with the special functions of Mathematical Physics & Chemistry can be derived as special cases